Genetic interactions of yeast eukaryotic translation initiation factor 5a (eIF5A) reveal connections to poly(A)-binding protein and protein kinase C signaling - Valentini, Sandro Roberto [UNESP] (2002)
The highly conserved eukaryotic translation initiation factor eIF5A has been proposed to have various roles in the cell, from translation to mRNA decay to nuclear protein export. To further our understanding of this essential protein, three temperature-sensitive alleles of the yeast TIF51A gene have been characterized. Two mutant eIF5A proteins contain mutations in a proline residue at the junction between the two eIFSA domains and the third, strongest allele encodes a protein with a single mutation in each domain, both of which are required for the growth defect. The stronger tif51A alleles cause defects in degradation of short-lived mRNAs, supporting a role for this protein in mRNA decay. A multicopy suppressor screen revealed six genes, the overexpression of which allows growth of a tif51A-1 strain at high temperature; these genes include PAB1, PKC1, and PKC1 regulators WSC1, WSC2, and WSC3. Further results suggest that eIFSA may also be involved in ribosomal synthesis and the WSC/PKC1 signaling pathway for cell wall integrity or related processes.